The influence of Malaysian consumers' attitudes and beliefs towards nutrition labels on food choices - Zainal Abidin, Zarinah (2001)
This survey investigated the impact of Malaysian consumers' beliefs and attitudes towards nutrition labeling on their choices of food/ purchasing behaviour. The use, influence and reliability of various sources of nutrition information were analysed using SPSS software. The findings generally suggested that there are a few demographic factors like gender, education and income associated with use of nutrition labeling. By identifying the determinants of consumer utilisation of food label information, more appropriate labeling policies and regulations can be initiated by the Government. In addition, the findings also showed that nutrition labeling, as one of the most widely available source of nutrition and food content can indirectly affect the demand for food products through changes in consumers' attitudes and beliefs towards the nutritional values of the products. Moreover, the consumers' feedback on the comprehensive use of nutrition labeling has given the food producers and manufacturers the opportunity and the incentive to enhance positive health-related attributes of their products.